Implikasi Perkembangan Peserta Didik dalam Pembelajaran di Kelas V Sekolah Dasar - Annisa Rahmadani; Armilah Armilah; Nabila Ulkhaira; Nadia Syafitri; Yunita Azhari; Ramadan Lubis (BADAN PENERBIT STIEPARI PRESS, 2025)
This research aims to analyze the implications of student development in learning in grade 5 elementary school. 11 year old Arya Rafasya, with a focus on five main aspects of development: physical, intellectual, emotional, spiritual and socio-moral. Using qualitative descriptive methods, data was collected through observation and in-depth interviews with Arya and her parents, which were then verified through triangulation to ensure the validity of the results. The research results show that Arya is in the ideal development category. Physically proportional and active, intellectually characterized by high curiosity and critical thinking abilities. Emotionally, Arya is able to manage her feelings well, although she needs further guidance. In the spiritual aspect, Arya begins to understand and carry out religious obligations, while in the social-moral aspect, Arya shows responsibility, honesty and empathy. This research emphasizes the importance of teacher and parent support to optimize children's holistic development.